2017
DOI: 10.1016/j.sjbs.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of some plant oils on diazinon induced hepatorenal toxicity in male rats

Abstract: Environmental pollution and exposure to environmental pollutants are still some of the major global health issues. Pesticides have been linked to a wide range of health hazards. The toxicity of pesticides depends on several factors such as its chemical properties, doses, exposure period, exposure methods, gender, genetics, age, nutritional status and physiological case of exposed individuals. Medicinal plants, natural products and nutrition continue to play a central role in the healthcare system of large prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 57 publications
1
16
0
6
Order By: Relevance
“…Furthermore, the antioxidant activities of sesame oil and canola oil were confirmed by the present evaluations of oxidative stress markers in rats subjected to malathion toxicity. The protective effects of sesame oil against several chemical toxicants associated with inhibition of the oxidative stress in experimental animals were reported by previous investigations (Liu et al, 2015;, Al-Attar et al, 2017. Al-Attar et al (2017; showed that the sesame oil attenuated the physiological disturbances and histopathological alterations induced by diazinon intoxication in male rats.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, the antioxidant activities of sesame oil and canola oil were confirmed by the present evaluations of oxidative stress markers in rats subjected to malathion toxicity. The protective effects of sesame oil against several chemical toxicants associated with inhibition of the oxidative stress in experimental animals were reported by previous investigations (Liu et al, 2015;, Al-Attar et al, 2017. Al-Attar et al (2017; showed that the sesame oil attenuated the physiological disturbances and histopathological alterations induced by diazinon intoxication in male rats.…”
Section: Discussionmentioning
confidence: 63%
“…Beberapa penelitian menunjukkan diazinon bersifat hepatotoksik pada tikus. Diazinon meningkatkan kadar serum alkalin fosfatase, alanin transaminase, aspartat trasaminase, gamma glutamyl transferase, bilirubin total, kreatinin, dan malondialdehid (Al-Attar et al, 2016). Diazinon mengandung radikal bebas yang menyebabkan stres oksidatif dan menginduksi terjadinya peroksidasi lipid (Oksay, 2012).…”
Section: Pendahuluanunclassified
“…Hepatoprotektor bekerja dengan mencegah adanya ikatan hidroksil yang diakibatkan oleh radikal bebas. Hepatoprotektor dapat ditemukan secara alami pada tumbuhan yang mengandung senyawa antioksidan (Al-Attar et al, 2016). Senyawa antioksidan ini diyakini dapat menetralkan efek negatif radikal bebas pada sel-sel tubuh.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…За аліментарного потрапляння діазинону в організм відбувається швидке його всмоктування у шлунково-кишковому тракті. У організмі діазинон метаболізує з утворенням токсичного метаболіту діазоксону (Aleksandrova and Goncharenko, 1983;Cox, 2000;Majeed and Al-Sereah Bahaa, 2012;Alam et al, 2015;Dankovych and Tumanov, 2016;Al-Attar et al, 2017).…”
unclassified